O gênero discursivo tira no ensino de língua portuguesa : uma proposta de trabalho - Melo, Christiane Renata Caldeira de (2015)
This is an result of a research derived from the Professional Master‟s Degree Program in Languages - PROFLETRAS - carried out in a public elementary school with seventh graders. We based our study in Bakhtin (1997), Rojo (2012), the National Curriculum Parameters (BRAZIL, 1998), Ramos (2012), Nepomuceno (2005), Ottoni (2007), Street (2012), among other authors and sources. Our methodology was based on the action research approach and the data collection was executed with reference to the teacher‟s diaries, as well as the professor‟s and researcher‟s. In this research, we investigated classes that were available at the Portal do Professor (in Portuguese), a website developed by the Brazilian Ministry of Education, about the Comic Strip Speech Genre (in Portuguese, GDT), which could explore multimodality, humor, irony and critics that are evident in the mentioned genre. Those classes were given to students/participants. Furthermore, we ascertained the presence and approach of GDT in Portuguese language textbooks that are used at the co-participant institution with the purpose to identify potential gaps when teaching it, thus creating a reading proposal of that gender based on the theoretical inputs that we made use of, taking into account the speech gender as a teaching object, aiming to incite rearrangements in the students concerned to reading, reading comprehension and interpretation. The reserach that we developed points out that the reading practices in which theory and practice are combined can help out Portuguese language students regarding theenhancement of the students‟reading competence.